Pengaruh Lamanya Penyimpanan terhadap Pertumbuhan Bakteri pada Nasi yang dimasak di Rice Cooker dengan Nasi yang Dikukus - Habib, Inayati; Aminudin, Muhamad (Universitas Muhammadiyah Yogyakarta, 2009)
Rice is an essential food for the Indonesian people, therefore its security must being important. Among different kind of cooking rice there are by using Electronic Rice Cooker and by steamed. The temperature influences profoundly against bacterial growth and its physiological activity. The endurance to temperature is different for each bacterial species. It is worth to investigate the different time storing of rice between being steamed and cooked Electronic Rice Cooker against bacterial growth. The aim of this study is to know the storing time between rice cooked by steamed and by Electronic Rice Cooker against bacterial growth which is still proper to be consumed The Research uses time series design method, with 0 hours, 2 hour, 4 hours, 6 hours and 8 hour depository. Rice counted 10 gram which taken from top, middle, and basic, left and right side. Then given 10 cc NaCl and diluted until 10000 times, then included to Petridis which contain jell count. The kind of bacteria made preparation smear colored with gram staining. The counting of bacterial amount after Petridis incubated in temperature ±37° C during 24 hours. The Result of preparation smear got 2 bacteria type that is gram (-) bacillus bacteria and of gram (+) coccids bacteria. Growth of germ number compare diametrical with improvement of time storing. At rice cook with Rice Cooker still competent up to standard consumed during 8 hour, while steamed rice during 6 hour. It can concluded that from growth of germ aspect, rice better cooked with Rice Cooker than steamed.Suhu sangat mempengaruhi pertumbuhan dan kegiatan fisiologi bakteri suatu mikroba atau bakteri. Daya tahan terhadap suhu berbeda bagi tiap spesies mikroba, sehingga perlu diteliti perbedaan lama penyimpanan nasi yang dimasak di Rice Cooker dan yang dikukus terhadap pertumbuhan kuman. Penelitian ini bertujuan untuk mengetahui lamanya waktu penyimpanan nasi yang dimasak dengan Rice Cooker dan nasi yang dikukus terhadap pertumbuhan bakteri yang masih memenuhi syarat untuk dikonsumsi. Metode Penelitian dengan metode time series design dengan waktu 0 jam, 2 jam, 4 jam, 6 jam dan 8 jam. Nasi ditimbang sebanyak 10 gram diambil dari bagian atas, tengah, bawah, samping kanan dan bagian samping kiri, kemudian diberi NaCl sebanyak 10 cc dan diencerkan sampai 10000X dan dimasukkan ke piring petri yang berisi count agar. Untuk melihat jenis kuman dibuat preparat apus yang diwarnai dengan cat gram. Penghitungan jumlah angka kuman setelah piring petri diinkubasi pada suhu ±37° C selama 24 jam. Hasil pengamatan preparat apus didapatkan 2 jenis kuman yaitu bakteri batang gram (-) dan kokus gram (+). Pertumbuhan angka kuman berbanding lurus dengan peningkatan lama penyimpanan. Pada nasi yang dimasak dengan Rice Cooker masih memenuhi syarat layak dikonsumsi selama 8 jam, sedangkan nasi yang dikukus selama 6 jam. Dapat disimpulkan bahwa dari segi angka kuman, nasi lebih baikjika dimasak dan disimpan di Rice Cooker daripada nasi yang dikukus.